Microstructure and heterogeneity of coal-bearing organic shale in the southeast Ordos Basin, China: Implications for shale gas storage - Yu, Rui; Wang, Zetang; Liu, Cheng; Zhang, Wenli; Zhu, Yuxuan; Tang, Mengmeng; Che, Qianjin (Frontiers in Earth Science, 2022)
In recent years, the eastern margin of Ordos Basin has attracted much attention as a key base for unconventional natural gas exploration. The pore-fracture structure is an important physical property of shale and provides places and channels for methane storage and migration. In this study, an integrated method of X-ray diffraction, total organic carbon (TOC), vitrinite reflectance (Ro), scanning electron microscopy (SEM), and low-temperature N2 adsorption was performed to reveal the microstructure and heterogeneity of coal-bearing organic shale in the southeast Ordos Basin. The result indicated that the studied shale belongs to the category of organic-rich shale with an average TOC content of 8.1% and reaches the dry gas stage with a mean Ro value of 2.41%. Hysteresis loop suggests the shapes of pore structure in shale samples are dominated by inkbottle, cylindrical pores or parallel-plate. A positive correlation between kaolinite and pore surface area indicates that kaolinite contributes greatly to micropores with a large specific surface area. Intense hydrocarbon generation promotes gas to escape from organic components' surfaces, thereby increasing the pore volume. Coal-bearing shales with high brittleness may contain more natural microfractures, increasing specific surface area and pore volume. The bocking effect of minerals in microfractures may reduce pore connectivity and connectivity and enhance shale heterogeneity. The pore volume and specific surface area of coal-bearing shale are closely related to the fractal dimensions. The high complexity of the shale microstructure may lead to the formation of more micropores, resulting in a decrease in the average pore size. Besides, organic and clay-hosted pores in coal-bearing shale with high maturity may well be the main storage space for methane, but the methane is mainly stored in organic pores in marine shale.